RENEGOTIATING LINGUISTIC IDENTITIES IN THE WAKE OF GLOBALIZATION - Pallavi Nimbalwar (European Scientific Journal, ESJ, 2015)
Globalization, as a world phenomenon has a direct relationship with language identities, Language loss and their chances of survival. Also, with English hailed as the lingua franca and a language for possibilities and prosperity, more and more world citizens are drawn towards it, often at the cost of their native languages. While it is true that we are all staunchly moving towards one world and language uniformity ensures homogenization, yet it clashes with the principle of preserving linguistic diversity. This poses certain questions like how is the globalization phenomenon related to issues of languages, culture and identity. What will be the effect of language loss; what roles does the linguist have to play in the process of language survival; why is language preservation needed? This paper scrutinizes language specific issues in the wake of globalization. The issues dealt with here are: status of world language and their chances of survival; factors contributing towards language loss and language survival; effects of language loss and need for language preservation; suggested steps towards language preservation.